Determinants of Female Labor Force Participation - Kiani, Adiqa Qausar (UI Scholars Hub, 2021)
There are many factors related to female entering the labor market. For example, household income, household expenditure, education and status of the head of the household (male/ female). The degree of correlation between each variable and female labor force participation rate varies throughout the country. This study focused on the factors due to which women enter in labor market. Tobit model is used for this analysis. It is concluded that education and household expenditures have positive but insignificant impact on the female LF, whereas household income and head of the household has negative impact on FLF. It is suggested that in order to improve the working condition of female labor force government should take necessary action, for example women education etc.